Rancang Bangun dan Uji Kinerja Mesin Pemarut Singkong Tipe Silinder untuk Produksi Tepung Tapioka - Darma Darma; Arif Faisol; Asti Sangaji Dahlia (Rekayasa, 2020)
The development of agroindustry in rural areas has a strategic role because raw materials are commonly produced in the areas. One of the industrial sub-sectors that has bright prospects to develop in rural agroindustries in Indonesia is tapioca flour processing industry. The most important operatiion units in tapioca processing is rasping or grating, which is mechanical disintegration of the tuber cell’s wall in order to free the starch granules and it suspended into the water during the extraction process.  The objective of this study was to design and test the performance of cassava rasping machine powered by gasoline engine.  In the experiment, three levels of cylinder rotation speed i.e. 1500 rpm, 2500 rpm and 3500 and two feeding methods of cassava tuber i.e. perpendicular and pararrel/longitudinal to the cylinder were examined. Results showed that combination of cylinder rotation speed and feeding methods significantly affect the rasping performances. The highest performance was obtained at the condition of cylinder rotation speed of 2500 rpm with feeding method perpendicular to the cylinder.  The performance of the machine at the condition were (1) rasping capacity 488,91  kg h-1, (2) starch percentage 42,28%, (3) starch loss in waste 7,61% and (4) rasping effect  84,92%.